How Garbage Gets From Trash Cans To Landfills - Erika L Shores (Mankato, MN, United States Capstone Press, 2016)
Where does the trash from last night's pizza party go after you take it to the curb? Easy-to-understand text explains how trash gets from homes to landfills or recycling centers and describes the role of the community workers who make it all possible.
Keywords: Sustainable cities and communities